The utilization of canola meal by young growing pigs - Seddon, Ian Robert (2012)
Four experiments, involving 140 pigs in performance and digestibility studies, were conducted to evaluate canola meal (CM) in comparison to soybean meal (SBM) as a protein supplement for young growing pigs. In experiments 1, 2 and 3, CM replaced 0, 50 or 100% of the SBM supplement on an isonitrogenous basis in isocaloric wheat-based diets for pigs fed from 14 to 32 kg. The effects of different lysine levels (0.74 or 0.84% total lysine) on performance were also studied. Feed intake and daily gains of pigs were reduced (P<0.05) when CM replaced 100% of the SBM supplement. Feed to gain ratios were similar (P>0.05) for all diets. Pigs fed diets formulated to contain 0.84% total lysine had nonsignificant (P>0.05) improved gains compared to pigs fed diets formulated to contain 0.74% total lysine. In experiment 4, pigs initially weighing 6 kg were fed a prestarter diet until an average final weight of 14 kg. Following this, a starter diet was fed for the weight range of 14 to 32 kg. Four isocaloric diets were formulated for each part of the experiment. CM and synthetic lysine replace o, 35, 69 or 82% of the SBM in the prestarter diets whereas CM alone replaced 0, 32, 51 or 100% of the SBM on an isonitrogenous basis in the starter diets. The prestarter diets were formulated to contain similar available lysine levels. Pigs fed the prestarter diets had similar (P>0.05) feed intakes, daily gains and feed to gain ratios. However, pigs fed the wheat-SBM starter diet had improved (P<0.05) feed intakes and daily gains compared to pigs fed the CM supplemented diets. Overall, pigs fed wheat-SBM diets from 6 to 32 kg in experiment 4 had improved (P<0.05) feed intakes and daily gains compared to pigs fed CM supplemented diets. Feed to gain ratios were similar (P>0.05) for all dietary treatments. Digestibility studies conducted in experiments 3 and 4 indicated there were treatment differences (P<0.05) observed for apparent fecal dry matter, nitrogen and amino acid digestibilities. Complete replacement of SBM by CM usually resulted in lower digestibility coefficients but the results were not always consistent since increasing the level of CM in the diets did not always cause reductions in apparent digestibility. In experiment 4, dry matter and nitrogen digestibility coefficients were higher by 3.6 and 2.0% respectively when pigs were fed the starter diets as compared to the prestarter diets indicating an age (adaptation) effect for the young pig. From these experiments it appeared complete (100%) replacement by CM caused reduced feed intakes and significantly lower gains. However partial (50%) replacement of SBM by CM (i.e. 12% in the diety) did not cause reduced performance thus CM could be included at up to 12% in diets for pigs 14 to 32 kg. The results of the prestarter period in experiment 4 indiated up to 14% CM and 0.5% added lysine could be used to replace 82% of the SBM without reducing performance of pigs over the weight range of 6 to 14 kg. The differences in digestibility coefficients did not help explain the reduced performance of pigs fed the CM supplemented diets.